Tempered glass, preparation method thereof and cover plate glass
By optimizing the component content and chemical strengthening process parameters of semi-finished glass, the problem of glass strengthening performance degradation caused by the increase of molten salt Na+ content is solved, extending the service life of molten salt, reducing costs and risks, and improving the mechanical properties of glass.
Patent Information
- Application Number
- CN202411205018.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-31
AI Technical Summary
In traditional glass chemical reinforcement processes, the increase in Na+ content of molten salt leads to a decrease in strengthening performance, making it difficult to extend the service life of molten salt while ensuring the glass reinforcement performance, thereby increasing raw material costs and production risks.
By optimizing the component content and chemical strengthening process parameters of semi-finished glass, especially by limiting the anti-attenuation coefficient ε and process conditions (temperature and time), the service life of molten salt is extended, and stress attenuation caused by excessive Na+ content is improved. Mechanical properties of glass.
It effectively extends the service life of molten salt, reduces raw material costs and production risks, and improves production efficiency. At the same time, it can predict and regulate the mechanical properties of reinforced glass to meet different application needs.
Smart Images

Figure SMS_7 
Figure SMS_8 
Figure SMS_9
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass products, and in particular to a tempered glass and a preparation method thereof, and a cover glass. Background Art
[0002] Glass is widely used in many fields, such as door and window glass in the construction industry, window glass and windshield of vehicles, cover glass of electronic touch devices, etc. After these glasses are processed and formed, they are usually chemically strengthened to enhance the mechanical strength, thermal stability and safety of glass products to meet more demanding application requirements.
[0003] Chemical strengthening is a process of placing semi-finished glass in molten salt for ion exchange to form a compressive stress layer on the glass surface. However, with the continuous use of molten salt, the strengthening performance of the resulting strengthened glass continues to decrease. After a certain period of use, even if the chemical strengthening process is adjusted, the ideal strengthening performance cannot be obtained. The only solution is to replace the molten salt, which has a short service life. Summary of the invention
[0004] Based on this, it is necessary to provide a strengthened glass and a preparation method thereof and a cover glass to solve the problem that the traditional method is difficult to extend the service life of the molten salt while ensuring the strengthening performance of the glass.
[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0006] In a first aspect of the present application, a method for preparing tempered glass is provided, comprising the following steps:
[0007] The semi-finished glass is placed in molten salt for chemical strengthening to prepare strengthened glass;
[0008] The semi-finished glass comprises the following components by mass fraction: 58% to 62% SiO2, 11% to 14.5% Al2O3, 12.5% to 15% Na2O, 4.5% to 6.5% K2O, 3% to 6% MgO and 0% to 3% B2O3;
[0009] Let a=58~62, b=11~14.5, c=12.5~15, d=4.5~6.5, e=3~6 and f=0~3, let the anti-attenuation coefficient of the semi-finished glass be ε=2.25b / (a+b)+0.55c / (c+d)+(0.16e+0.84f) / (e+f), let the temperature and time of the chemical strengthening treatment be T and t respectively, and satisfy the following conditions:
[0010] (1) ε ≥ 0.940;
[0011] (2) 75≤T×t×exp(-ε-1.125)≤110.
[0012] In one of the embodiments, the following condition is satisfied: ε≤1.327.
[0013] In one embodiment, the semi-finished glass is placed in molten salt for chemical strengthening, comprising the following steps:
[0014] Placing the semi-finished glass in a molten salt with a sodium ion content of 0 ppm for chemical strengthening treatment to prepare a first strengthened glass, and placing the semi-finished glass in a molten salt with a sodium ion content of 10820 ppm for chemical strengthening treatment to prepare a second strengthened glass;
[0015] The surface compressive stress of the first strengthened glass is CS0 and the stress layer depth is DOL0, and the surface compressive stress of the second strengthened glass is CS4 and the stress layer depth is DOL4, satisfying the following conditions:
[0016] (1) ;
[0017] (2) .
[0018] In one embodiment, the following conditions are met: T=435°C~445°C, t=1.8h~2.2h.
[0019] In one of the embodiments, the semi-finished glass further includes ZrO2 with a mass fraction of 0.5% to 1.3%.
[0020] In one embodiment, the method for preparing the semi-finished glass comprises the following steps:
[0021] preparing batch materials according to the contents of the components of the semi-finished glass;
[0022] The batch materials are subjected to melting treatment, forming treatment and annealing treatment to prepare the semi-finished glass.
[0023] In one embodiment, the temperature of the melting process is 1600°C~1680°C.
[0024] In one embodiment, the melting process takes 4 hours to 10 hours.
[0025] In one embodiment, the annealing temperature is 700°C to 760°C.
[0026] In one embodiment, the annealing treatment time is 2h~6h.
[0027] In a second aspect of the present application, a tempered glass is provided, which is prepared by the method for preparing tempered glass as described above.
[0028] In one embodiment, the surface compressive stress of the tempered glass is 750MPa-950MPa.
[0029] In one embodiment, the stress layer depth of the strengthened glass is 32 μm-45 μm.
[0030] In one embodiment, the falling height of the tempered glass is 68 cm to 100 cm.
[0031] In one embodiment, the four-point bending strength of the tempered glass is 170 MPa-210 MPa.
[0032] In a third aspect of the present application, a cover glass is provided, which is made of the tempered glass as described above.
[0033] This application has at least the following beneficial effects:
[0034] According to the influence of the formula of semi-finished glass on mechanical properties and strengthening properties, the content of each component and the anti-attenuation coefficient are limited, and the semi-finished glass is adapted to a specific chemical strengthening process, so that the semi-finished glass has excellent strengthening properties and avoids Na in the molten salt. + Excessive content leads to a significant attenuation of stress, which effectively prolongs the service life of the molten salt, thereby reducing raw material costs, improving production efficiency and reducing safety risks. In addition, according to the formula of the semi-finished glass and the process parameters of the chemical strengthening treatment provided by this application, the mechanical properties of the strengthened glass can also be predicted, which has a guiding role. When facing specific application requirements, the formula of the semi-finished glass and the chemical strengthening process can be accurately controlled, which is conducive to reducing the cost and improving production efficiency. DETAILED DESCRIPTION
[0035] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0037] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0038] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0039] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0041] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0042] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.
[0043] Glass can be classified into soda-lime glass, lead silicate glass, aluminosilicate glass, borosilicate glass and quartz glass according to its chemical composition. Among them, aluminosilicate glass with an Al2O3 content of more than 6wt.% is called high-aluminum glass. Its intrinsic mechanical strength and chemical strengthening properties are significantly better than those of ordinary soda-lime glass, and it can be used in scenes with high requirements for mechanical properties or high-end products.
[0044] In the chemical strengthening process, pure KNO3 molten salt is usually used to exchange ions with glass to form a compressive stress layer on the glass surface. + will enter the molten salt, making the Na + The content of KNO3 increases, and the molten salt changes from KNO3 molten salt to a mixed molten salt composed of KNO3 and NaNO3. This results in the Na in the glass and molten salt + and K + The concentration difference decreases, which weakens the driving force of ion exchange, ultimately affecting the strengthening properties of the glass, such as the surface compressive stress (Compressed Stress, CS) and the depth of stress layer (Depth of Layers, DOL).
[0045] Further investigation revealed that as the Na + The content increases, and the K entering the glass + The decrease in K weakens the "crowding effect" produced by ion exchange, thus significantly reducing the CS value of the tempered glass. + The diffusion depth is basically not affected, so the DOL value is less affected. + The main problem caused by the increase in content is the decrease in CS value.
[0046] Generally speaking, when the Na + When the content reaches about 7000ppm, the attenuation of the CS value has reached an unacceptable level. At this time, even if the process parameters such as the time and temperature of chemical strengthening are adjusted, the ideal strengthening performance cannot be obtained, and new pure KNO3 molten salt can only be replaced. Depending on the performance requirements of the strengthened glass and the processing volume, the replacement frequency of the molten salt is also different. The typical replacement frequency is once every six months. However, the processing volume of chemical strengthening is large, the amount of molten salt used is large, and the recovery value of waste molten salt is low. Therefore, frequent replacement of molten salt will result in excessively high cost of strengthened glass. At the same time, the downtime period caused by the replacement of molten salt is long, which affects production efficiency and poses a greater risk of safe operation. Therefore, it is necessary to develop a chemical strengthening process that can extend the service life of the molten salt as much as possible while obtaining good strengthening performance.
[0047] Based on this, in a first aspect, the present application provides a method for preparing tempered glass.
[0048] In some embodiments, a method for preparing a strengthened glass comprises the following steps:
[0049] The semi-finished glass is placed in molten salt for chemical strengthening to prepare strengthened glass;
[0050] The semi-finished glass includes the following components by mass fraction: 58% to 62% SiO2, 11% to 14.5% Al2O3, 12.5% to 15% Na2O, 4.5% to 6.5% K2O, 3% to 6% MgO and 0% to 3% B2O3;
[0051] Let a=58~62, b=11~14.5, c=12.5~15, d=4.5~6.5, e=3~6 and f=0~3, let the anti-attenuation coefficient of the semi-finished glass be ε=2.25b / (a+b)+0.55c / (c+d)+(0.16e+0.84f) / (e+f), let the temperature and time of the chemical strengthening treatment be T and t respectively, and satisfy the following conditions:
[0052] (1) ε ≥ 0.940;
[0053] (2) 75≤T×t×exp(-ε-1.125)≤110.
[0054] According to the influence of the formula of semi-finished glass on mechanical properties and strengthening properties, the content of each component and the anti-attenuation coefficient are limited, and the semi-finished glass is adapted to a specific chemical strengthening process, so that the semi-finished glass has excellent strengthening properties and avoids Na in the molten salt. + Excessive content leads to a significant attenuation of stress, which effectively prolongs the service life of the molten salt, thereby reducing raw material costs, improving production efficiency and reducing safety risks. In addition, according to the formula of the semi-finished glass and the process parameters of the chemical strengthening treatment provided by this application, the mechanical properties of the strengthened glass can also be predicted, which has a guiding role. When facing specific application requirements, the formula of the semi-finished glass and the chemical strengthening process can be accurately controlled, which is conducive to reducing the cost and improving production efficiency.
[0055] Silicon dioxide (SiO2) is the main component of the glass skeleton and has an effect on improving the mechanical strength of the glass, but it will increase the viscosity of the glass. If the mass fraction of SiO2 is less than 58%, the glass forming performance is poor, and the strength and weather resistance are insufficient; if the mass fraction of SiO2 exceeds 62%, the solubility of the glass deteriorates. The mass fraction of SiO2 is 58%~62%, that is, a=58~62. As an example, the mass fraction of SiO2 can be 58%, 58.5%, 59%, 59.5%, 60%, 60.5%, 61%, 61.5% or 62%.
[0056] Alumina (Al2O3) is a necessary component that can improve the mechanical strength and strengthening properties of glass, but it will increase the viscosity of the glass and make it more difficult to clarify. If the mass fraction of Al2O3 is lower than 11%, the mechanical strength and strengthening properties of the glass are insufficient. If the mass fraction of Al2O3 is higher than 14.5%, the viscosity of the glass is too high and it is difficult to clarify, and the melting quality is reduced. The mass fraction of Al2O3 is 11%~14.5%, that is, b=11~14.5. As an example, the mass fraction of Al2O3 can be 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14% or 14.5%.
[0057] Sodium oxide (Na2O) can significantly improve the solubility of glass and is a necessary component, but it will reduce the chemical stability of glass and increase the thermal expansion coefficient. If the mass fraction of Na2O is lower than 12.5%, the solubility of glass will be poor. At the same time, too low Na2O content will lead to Na+ in the glass and molten salt. + The concentration difference of glass decreases, and the glass + The adaptability of molten salt with too high a content is deteriorated; if the mass fraction of Na2O is higher than 15%, the thermal expansion coefficient of the glass is too large and the processing yield is reduced. The mass fraction of Na2O is 12.5%~15%, that is, c=12.5~15. As an example, the mass fraction of Na2O can be 12.5%, 13%, 13.5%, 14%, 14.5% or 15%.
[0058] Potassium oxide (K2O) is an essential component that can improve the meltability of glass. K2O and Na2O can also work together to produce a "mixed alkali effect" to improve the mechanical strength of the glass and the DOL value after strengthening. If the mass fraction of K2O is lower than 4.5%, the meltability of the glass is poor; if the mass fraction of K2O is higher than 6%, the thermal expansion coefficient of the glass is too large. The mass fraction of K2O is 4.5%~6.5%, that is, d=4.5~6.5. As an example, the mass fraction of K2O can be 4.5%, 5%, 5.5%, 6% or 6.5%.
[0059] Magnesium oxide (MgO) is an essential component. It can reduce the viscosity of glass liquid at high temperature, promote the melting and clarification of glass, reduce the thermal expansion coefficient of glass, increase the CS value, but reduce the DOL value. If the mass fraction of MgO is lower than 3%, the solubility of the glass deteriorates, and the thermal expansion coefficient increases, resulting in insufficient CS value. If the mass fraction of MgO is higher than 6%, the DOL value of the glass decreases, and it is difficult to achieve the ideal strengthening performance. The mass fraction of MgO is 3%~6%, that is, e=3~6. As an example, the mass fraction of MgO can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.
[0060] Boron oxide (B2O3) can reduce the high temperature viscosity and thermal expansion coefficient of glass, thereby increasing the CS value, but it will reduce the DOL value. It is not a necessary component. If the mass fraction of B2O3 is higher than 3%, the glass is difficult to homogenize, the quality is reduced, and the DOL value is insufficient. The mass fraction of B2O3 is 0%~3%, that is, f=0~3. As an example, the mass fraction of B2O3 can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.
[0061] In some embodiments, the semi-finished glass further comprises ZrO2 in an amount of 0.5% to 1.3% by mass.
[0062] Zirconia (ZrO2) has no effect on the anti-attenuation coefficient of semi-finished glass, that is, at different Na + The difference in CS after chemical strengthening in molten salt with different contents is very small. When improving the anti-attenuation coefficient ε of semi-finished glass, there is no need to adjust the ZrO2 content. On the other hand, ZrO2 can improve the weather resistance of glass and increase the CS value by reducing the thermal expansion coefficient of glass, but it will increase the viscosity of glass. Adding an appropriate amount of anti-attenuation coefficient ε is beneficial to improving the CS value of tempered glass, but if the mass fraction of ZrO2 is higher than 1.3%, the solubility of the glass deteriorates. As an example, the mass fraction of ZrO2 can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2% or 1.3%.
[0063] In some embodiments, the method for preparing semi-finished glass comprises the following steps:
[0064] Prepare batch materials according to the content of each component of semi-finished glass;
[0065] The batch materials are subjected to melting treatment, forming treatment and annealing treatment to prepare semi-finished glass.
[0066] In some embodiments, the temperature of the melt treatment is 1600° C. to 1680° C. As an example, the temperature of the melt treatment may be 1600° C., 1610° C., 1620° C., 1630° C., 1640° C., 1650° C., 1660° C., 1670° C., or 1680° C.
[0067] In some embodiments, the melting treatment time is 4 hours to 10 hours. As an example, the melting treatment time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours or 10 hours.
[0068] In some embodiments, the annealing temperature is 700° C. to 760° C. As an example, the annealing temperature may be 700° C., 705° C., 710° C., 715° C., 720° C., 725° C., 730° C., 735° C., 740° C., 745° C., 750° C., 755° C., or 760° C.
[0069] In some embodiments, the annealing time is 2 hours to 6 hours. As an example, the annealing time can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0070] In some embodiments, the melting process includes the following steps: placing the batch material in a crucible, heating to 1630°C~1680°C, and keeping warm for 5h~7h; cooling to 1600°C~1620°C, and keeping warm for 0.5h~2h to prepare molten glass liquid.
[0071] In some embodiments, the molding process includes the following steps: preheating the mold to 450° C. to 550° C. and pouring molten glass into the mold. The mold may be a ceramic mold or a graphite mold, and the shape of the mold is not particularly limited, and may be rectangular, circular or irregular.
[0072] In some embodiments, the annealing treatment includes the following steps: after the molten glass in the mold is hardened, annealing at 700° C. to 760° C. for 2 h to 6 h.
[0073] In some embodiments, after the annealing treatment, the following steps are further included: cutting, grinding and polishing to obtain semi-finished glass. The size of the semi-finished glass obtained after polishing is not particularly limited. In some specific examples, the size of the semi-finished glass can be 150 mm×70 mm×1.1 mm.
[0074] The following is the semi-finished glass with different Na + The stress properties of strengthened glass can be tested by the following methods:
[0075] (1) Use FSM-6000LE stress meter to perform stress test and obtain CS value (in MPa) and DOL value (in μm);
[0076] (2) Use a PT-706 drop ball tester to perform a drop ball test: Use a 130g steel ball to hit the center point of the tempered glass once, and gradually increase the test height in steps of 5 cm until the tempered glass breaks. Record the height when it breaks, and fit the data using the Weibull distribution to obtain its B10 value (that is, under the Weibull distribution, the test result has a 90% probability of being higher than this value), which is recorded as the drop ball height H (in cm);
[0077] (3) A four-point bending (4PB) test was performed using a PT-307A bending strength tester to obtain the B10 value under the Weibull distribution, which was recorded as the four-point bending strength S (in MPa).
[0078] Semi-finished glass for different Na + The adaptability of molten salt with different Na content can be measured by the anti-attenuation coefficient ε. The larger the anti-attenuation coefficient ε, the better the semi-finished glass will be in different Na + The smaller the difference in CS value after chemical strengthening in molten salt with high Na content, the smaller the difference in CS value after chemical strengthening in molten salt with high Na content. + The smaller the attenuation of the CS value after chemical strengthening in the molten salt with a higher content, the more suitable it is for high Na + In this application, the anti-attenuation coefficient ε of the semi-finished glass and the content of each component have the following relationship: ε=2.25b / (a+b)+0.55c / (c+d)+(0.16e+0.84f) / (e+f). In order to make the semi-finished glass + The attenuation amplitude of the CS value after strengthening in the molten salt with a content of 1.5477% is small. The anti-attenuation coefficient ε and the process parameters of the chemical strengthening treatment temperature T (in °C) and time t (in h) should meet the following conditions: (1) ε ≥ 0.940; (2) 75 ≤ T × t × exp (-ε-1.125) ≤ 110.
[0079] In some embodiments, the following condition is satisfied: ε≤1.327. That is, the anti-attenuation coefficient ε satisfies the following condition: 0.940≤ε≤1.327. As an example, the anti-attenuation coefficient ε of the semi-finished glass may be 0.940, 0.960, 0.980, 1.000, 1.020, 1.050, 1.080, 1.100, 1.120, 1.150, 1.180, 1.200, 1.220, 1.250, 1.280, 1.300, 1.320 or 1.327.
[0080] The larger the anti-attenuation coefficient ε is, the stronger the stress attenuation resistance of the semi-finished glass after chemical strengthening is, and the more suitable it is for high Na +Under the premise of meeting the content of each component, the maximum value of the anti-attenuation coefficient ε is 1.327. If the anti-attenuation coefficient ε is to be further increased, the content of each component will not meet the formula requirements of the semi-finished glass, which will lead to the deterioration of other properties such as strength and linear expansion coefficient, which is not conducive to the preparation of tempered glass with excellent comprehensive performance.
[0081] In some embodiments, the sodium ions (Na + ) content is 0ppm~10820ppm. As an example, Na in molten salt + The content may be 0 ppm, 100 ppm, 500 ppm, 800 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm, 10200 ppm, 10500 ppm, 10800 ppm or 10820 ppm.
[0082] In traditional technology, Na in molten salt + When the content reaches 7000ppm, the CS attenuation of the tempered glass has reached an unacceptable level. Generally speaking, in order to obtain good stress performance, the Na + When the content reaches 4000ppm, the molten salt needs to be replaced. + When the content reaches 10820ppm, the CS attenuation of the tempered glass is relatively small, so the service life of the molten salt can be greatly extended. According to the traditional processing volume and processing frequency, the service life can be increased by about 8 months, which significantly reduces the raw material cost and improves production efficiency.
[0083] In some embodiments, the molten salt includes a potassium nitrate (KNO3) molten salt having a mass fraction of 96% to 100% and a sodium nitrate (NaNO3) molten salt having a mass fraction of 0% to 4%. As an example, the mass fraction of the KNO3 molten salt may be 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5% or 100%, and the mass fraction of the NaNO3 molten salt may be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%.
[0084] In this application, if the molten salt includes 100% KNO3 molten salt by mass, then the Na + If the molten salt includes 96% KNO3 molten salt and 4% NaNO3 molten salt, then the Na + The content is 10820ppm.
[0085] In some embodiments, placing the semi-finished glass in a molten salt for chemical strengthening treatment comprises the following steps: placing the semi-finished glass in a molten salt with a sodium ion content of 0 ppm for chemical strengthening treatment to prepare a first strengthened glass, and placing the semi-finished glass in a molten salt with a sodium ion content of 10820 ppm for chemical strengthening treatment to prepare a second strengthened glass.
[0086] It can be understood that the temperature and time of the two chemical strengthening treatments were kept the same; Na + The molten salt with a content of 0 ppm, that is, the molten salt includes 100% KNO3 molten salt by mass; Na + The molten salt content is 10820 ppm, that is, the molten salt includes 96% by mass molten salt of KNO3 and 4% by mass molten salt of NaNO3.
[0087] The surface compressive stress of the first tempered glass is CS0, the stress layer depth is DOL0, the ball drop height is H0, and the four-point bending strength is S0. The surface compressive stress of the second tempered glass is CS4, the stress layer depth is DOL4, the ball drop height is H4, and the four-point bending strength is S4.
[0088] Given that Na in molten salt + The main problem caused by the increase in content is the decrease in CS value. This application uses ∆CS=CS0-CS4 to evaluate the attenuation of CS value. Through in-depth optimization of chemical strengthening process parameters and the content of each component, it is found that ∆CS satisfies the following relationship: ∆CS=CS0-CS4=T×t×exp(-ε-1.125). In order to make the second strengthened glass also obtain good stress properties, ∆CS should be controlled in the range of 75MPa~110MPa, that is, 75≤T×t×exp(-ε-1.125)≤110. According to this relationship, it can be predicted to a certain extent that under different Na + The CS value of the strengthened glass obtained by strengthening in a molten salt with a certain content of ΔCS can be used to adaptively adjust the chemical strengthening process parameters and the content of each component. As an example, ΔCS can be 75MPa, 80MPa, 85MPa, 90MPa, 95MPa, 100MPa, 105MPa or 110MPa.
[0089] In addition to using ∆CS to evaluate the attenuation of the CS value, the present application also uses H′=H4 / H0 and S′=S4 / S0 to evaluate the attenuation of mechanical properties. In order to obtain good mechanical properties for the second tempered glass, H′ should be controlled between 0.886 and 0.925, and S′ should be controlled between 0.918 and 0.950. As an example, H′ can be 0.886, 0.890, 0.895, 0.900, 0.905, 0.910, 0.915, 0.920 or 0.925, and S′ can be 0.918, 0.920, 0.925, 0.930, 0.935, 0.940, 0.945 or 0.950.
[0090] In some embodiments, H′ satisfies the following relationship:
[0091] (1) ; (2) .
[0092] In some embodiments, S′ satisfies the following relationship:
[0093] (1) ; (2) .
[0094] In some embodiments, the following conditions are met: T=435°C~445°C, t=1.8h~2.2h.
[0095] When the temperature of chemical strengthening treatment is 435℃~445℃ and the time is 1.8h~2.2h, it can ensure that the strengthened glass meets the following three conditions at the same time: ∆CS=75MPa~110MPa, H′=0.886~0.925, S′=0.918~0.950.
[0096] If the temperature of the chemical strengthening treatment is lower than 435°C, the ion exchange is insufficient and the stress decay cannot be effectively resisted; if the temperature of the chemical strengthening treatment is higher than 445°C, the decomposition of the molten salt is aggravated and the purpose of extending the service life of the molten salt cannot be achieved. As an example, the temperature of the chemical strengthening treatment can be 435°C, 436°C, 437°C, 438°C, 439°C, 440°C, 441°C, 442°C, 443°C, 444°C or 445°C.
[0097] If the chemical strengthening treatment time is too short, the ion exchange is insufficient and the stress decay cannot be effectively resisted; if the chemical strengthening treatment time is too long, the CS value will further decay and the production efficiency will be reduced. As an example, the chemical strengthening treatment time can be 1.8h, 1.9h, 2.0h, 2.1h or 2.2h.
[0098] In a second aspect of the present application, a tempered glass is provided, which is prepared by the method for preparing tempered glass as described above.
[0099] In some embodiments, the surface compressive stress (CS) of the strengthened glass is 750 MPa to 950 MPa. As an example, the CS value of the strengthened glass can be 750 MPa, 780 MPa, 800 MPa, 820 MPa, 850 MPa, 880 MPa, 900 MPa, 920 MPa or 950 MPa.
[0100] In some embodiments, the depth of stress layer (DOL) of the strengthened glass is 32 μm to 45 μm. As an example, the DOL value of the strengthened glass may be 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm or 45 μm.
[0101] In some embodiments, the height of the ball drop of the tempered glass is 68 cm to 100 cm. As an example, the height of the ball drop of the tempered glass can be 68 cm, 70 cm, 75 cm, 80 cm, 85 cm, 90 cm, 95 cm or 100 cm.
[0102] In some embodiments, the four-point bending strength of the strengthened glass is 170 MPa to 210 MPa. As an example, the four-point bending strength of the strengthened glass can be 170 MPa, 175 MPa, 180 MPa, 185 MPa, 190 MPa, 195 MPa, 200 MPa, 205 MPa or 210 MPa.
[0103] In a third aspect of the present application, a cover glass is provided, which is made of the tempered glass as described above.
[0104] It can be understood that the tempered glass prepared in the present application has a higher surface compressive stress, a higher stress layer depth, a higher ball drop height and a higher four-point bending strength. The cover glass made of tempered glass has better mechanical strength, which effectively improves the drop resistance and scratch resistance of the cover glass, thereby increasing the service life of the cover glass.
[0105] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0106] Example 1
[0107] (1) Preparation of semi-finished glass:
[0108] Please refer to Table 1. Based on 1400g of molten glass liquid, calculate and weigh the corresponding raw materials of SiO2, Al2O3, Na2O, K2O, MgO, ZrO2 and B2O3, grind and mix them evenly to obtain a batch material; place the batch material in a platinum crucible, and place the platinum crucible in a lifting furnace, heat it to 1650℃, keep it warm for 6 hours, then reduce it to 1600℃, and keep it warm for 1 hour to obtain molten glass liquid; preheat a rectangular graphite mold to 500℃, and pour the molten glass liquid into the rectangular graphite mold. After the molten glass liquid hardens, transfer it to an annealing furnace that has been heated to 720℃, keep it warm for 4 hours, and cool it to room temperature with the furnace; take it out, cut it into thin slices, grind and polish it on both sides to obtain a semi-finished glass with a size of 150mm×70mm×1.1mm (L×W×H).
[0109] (2) Chemical strengthening treatment:
[0110] The semi-finished glass was placed in pure KNO3 molten salt and strengthened at 440°C for 2 hours to obtain the first strengthened glass; the semi-finished glass was placed in a mixed molten salt composed of KNO3 molten salt and NaNO3 molten salt with a mass ratio of 96:4, and strengthened at 440°C for 2 hours to obtain the second strengthened glass.
[0111] Embodiments 2 to 20
[0112] The content of each component of the semi-finished glass of Examples 2 to 20, and the temperature and time of the chemical strengthening treatment are shown in Tables 1 to 4.
[0113] Comparative Examples 1 to 10
[0114] The contents of the components of the semi-finished glasses of Comparative Examples 1 to 10, and the temperature and time of the chemical strengthening treatment are shown in Tables 5 to 6.
[0115] Test Case
[0116] After the chemical strengthening treatment, the first strengthened glass and the second strengthened glass in each embodiment and each comparative example were cleaned and dried; a stress test was performed using a FSM-6000LE stress meter to obtain CS0, DOL0, CS4 and DOL4, and ΔCS was calculated; a drop ball test was performed using a PT-706 drop ball tester to obtain H0 and H4, and H′ was calculated; and a four-point bending (4PB) test was performed using a PT-307A bending strength tester to obtain S0 and S4, and S′ was calculated. The results are shown in Tables 1 to 6.
[0117] According to Tables 1 to 6, the contents of the components of the semi-finished glasses of Examples 1 to 20 all meet the requirements of the preset formula, the anti-attenuation coefficient ε is in the range of 0.940 to 1.327, and the mechanical properties of the obtained second strengthened glass can generally reach 90% of the mechanical properties of the first strengthened glass, that is, the Na in the molten salt is 0.940 to 1.327. + When the content reaches 10820ppm, the attenuation of the mechanical properties of the second strengthened glass can be controlled within 10%, so + The molten salt with high content has good adaptability and effectively prolongs the service life of the molten salt.
[0118] The contents of each component of the semi-finished glass of Comparative Example 1 meet the requirements of the preset formula, but the anti-attenuation coefficient ε<0.940 is only 0.868; ΔCS=176MPa, indicating that the CS value of the second strengthened glass is seriously attenuated; H′=0.798, S′=0.849, indicating that the ball drop height and four-point bending strength of the second strengthened glass are also significantly attenuated.
[0119] Comparative Example 3 is almost the same as Example 8, except that: the mass fraction of Al2O3 in Comparative Example 3 is lower than 11%, which results in a slightly larger ΔCS value of 148 MPa; H′=0.842, S′=0.868, and the attenuation of mechanical properties is relatively large.
[0120] Comparative Example 4 is almost the same as Example 4, except that the mass fraction of B2O3 in Comparative Example 4 is higher than 3%. In this case, the contribution to stress decay is negative, resulting in a large ΔCS value, while H′ and S′ are low, and the mechanical properties are not ideal.
[0121] Comparative Example 5 is almost the same as Example 16, except that the mass fraction of Na2O in Comparative Example 5 is lower than 12.5%, resulting in the difference between it and Na2O in the molten salt. + The decrease in concentration difference is not conducive to ion exchange, so the ΔCS value is relatively large, while H′ and S′ are both low.
[0122] Comparative Example 6 is almost the same as Example 5, except that the mass fraction of MgO in Comparative Example 6 is higher than 6%, resulting in a slightly larger ΔCS value, while H′ and S′ are both lower.
[0123] The contents of the components of the semi-finished glass of Comparative Example 2 are consistent with those of Example 1, and the anti-attenuation coefficient ε is also the same, but the process parameters of the chemical strengthening treatment are different. In Comparative Example 2, the semi-finished glass is strengthened at 410° C. for 1.5 h, which results in insufficient ion exchange and insufficient anti-attenuation capability, and ΔCS also reaches 176 MPa, and H′ and S′ are further reduced.
[0124] The difference between Comparative Examples 7 and 8 and Example 10 is only the strengthening temperature. The strengthening temperature used in Comparative Example 7 is 410°C, which results in insufficient ion exchange and insufficient anti-fading ability. The strengthening temperature used in Comparative Example 8 is 460°C, which results in excessive ion exchange and has entered the stress relaxation stage, resulting in insufficient anti-fading ability. Therefore, ΔCS, H′ and S′ of Comparative Examples 7 and 8 do not meet the requirements.
[0125] The difference between Comparative Examples 9 and 10 and Example 10 is only the strengthening time. The strengthening time used in Comparative Example 9 is 1.6 hours, which leads to insufficient ion exchange and insufficient anti-decay ability. The strengthening time used in Comparative Example 10 is 2.5 hours, which leads to excessive ion exchange and has entered the stress relaxation stage, resulting in insufficient anti-decay ability. Therefore, ΔCS, H′ and S′ of Comparative Examples 9 and 10 do not meet the requirements.
[0126] In summary, this application has deeply optimized the content of each component of semi-finished glass, and adapted it with an accurate chemical strengthening process, which greatly extends the service life of the molten salt, thereby achieving the purpose of reducing raw material costs, improving production efficiency and reducing safety risks. On the other hand, the mechanical properties of the strengthened glass can be predicted based on the content of each component of the semi-finished glass and parameters such as the chemical strengthening process, which has a guiding role and is convenient for adjusting the formula and process when there are specific needs.
[0127] Table 1. Relevant parameters of tempered glass of Examples 1 to 5
[0128]
[0129] Table 2. Relevant parameters of tempered glass of Examples 6 to 10
[0130]
[0131] Table 3. Relevant parameters of tempered glass of Examples 11 to 15
[0132]
[0133] Table 4. Relevant parameters of tempered glass of Examples 16 to 20
[0134]
[0135] Table 5. Relevant parameters of tempered glass of comparative examples 1 to 5
[0136]
[0137] Table 6. Related parameters of tempered glass of comparative examples 6 to 10
[0138]
[0139] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0140] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.
Claims
1. A method for preparing tempered glass, characterized in that: The following steps are involved: The semi-finished glass is placed in molten salt for chemical strengthening treatment to prepare strengthened glass; The semi-finished glass comprises the following components by mass fraction: 58% to 62% SiO2, 11% to 14.5% Al2O3, 12.5% to 15% Na2O, 4.5% to 6.5% K2O, 3% to 6% MgO and 0% to 3% B2O3; Let a=58~62, b=11~14.5, c=12.5~15, d=4.5~6.5, e=3~6 and f=0~3, let the anti-attenuation coefficient of the semi-finished glass be ε=2.25b / (a+b)+0.55c / (c+d)+(0.16e+0.84f) / (e+f), let the temperature and time of the chemical strengthening treatment be T and t respectively, and satisfy the following conditions: (1) ε ≥ 0.940; (2) 75≤T×t×exp(-ε-1.125)≤110.
2. The method for preparing tempered glass according to claim 1, wherein: The following conditions are met: ε≤1.
327.
3. The method for preparing tempered glass according to claim 2, wherein: The semi-finished glass is placed in molten salt for chemical strengthening, including the following steps: Placing the semi-finished glass in a molten salt with a sodium ion content of 0 ppm for chemical strengthening treatment to prepare a first strengthened glass, and placing the semi-finished glass in a molten salt with a sodium ion content of 10820 ppm for chemical strengthening treatment to prepare a second strengthened glass; The surface compressive stress of the first strengthened glass is CS0 and the stress layer depth is DOL0, and the surface compressive stress of the second strengthened glass is CS4 and the stress layer depth is DOL4, satisfying the following conditions: (1) ; (2) 。 4. The method for preparing tempered glass according to any one of claims 1 to 3, wherein: The following conditions are met: T=435℃~445℃, t=1.8h~2.2h.
5. The method for preparing tempered glass according to any one of claims 1 to 3, wherein: The semi-finished glass further comprises ZrO2 with a mass fraction of 0.5% to 1.3%.
6. The method for preparing tempered glass according to any one of claims 1 to 3, characterized in that: The method for preparing the semi-finished glass comprises the following steps: preparing batch materials according to the contents of the components of the semi-finished glass; The batch material is subjected to melting treatment, forming treatment and annealing treatment to prepare the semi-finished glass.
7. The method for preparing tempered glass according to claim 6, wherein: One or more of the following conditions are met: (1) The temperature of the melting treatment is 1600°C to 1680°C; (2) The melting treatment time is 4h~10h; (3) The annealing temperature is 700°C to 760°C; (4) The annealing treatment time is 2h~6h.
8. A tempered glass, characterized in that: The tempered glass is prepared by the method for preparing the tempered glass according to any one of claims 1 to 7.
9. The tempered glass according to claim 8, wherein: The tempered glass satisfies one or more of the following conditions: (1) The surface compressive stress of the tempered glass is 750 MPa to 950 MPa; (2) The stress layer depth of the tempered glass is 32 μm to 45 μm; (3) The falling height of the tempered glass is 68 cm to 100 cm; (4) The four-point bending strength of the tempered glass is 170 MPa to 210 MPa.
10. A cover glass, characterized in that: Made of the tempered glass as claimed in claim 8 or 9.
